Drivers of Plant-Availability of Phosphorus from Thermally Conditioned Sewage Sludge as Assessed by Isotopic Labeling - Andriamananjara, Andry; Rabeharisoa, Lilia; Prud’homme, Loïc; Morel, Christian (Frontiers in Nutrition, 2016)
Urban sewage sludge is a potential source of phosphorus (P) for agriculture and represents an alternative way to recycle P as fertilizer. However, the use of thermally conditioned sewage sludge (TCSS) required an accurate assessment of its value as P-fertilizer. This work aimed at assessing the plant-availability of P from TCSS. Uptake of P by a mixture of ryegrass and fescue from TCSS and triple super phosphate (TSP) fertilizers was studied using 32P-labeling technique in a greenhouse experiment. Phosphorus was applied at the rate of 50 mg P kg−1.We also conducted incubation experiments considering the same treatments to assess soil microbial respiration. Applications of TCSS and TSP increased plant P uptake that is related to the root P acquisition. The P taken up by plant from soil plant-available P was lower for control compared to TSP or TCSS that was attributed to the increase of root interception of soil P. The contribution of TSP to ryegrass nutrition (Pdff%) was 55% with 22% of the applied P which was taken up by plants (CPU%). The Pdff value for TCSS was 56% with 14% of fertilizer P recovery (CPU%). Shoot biomass and total P uptake from TCSS were lower than those from TSP. As a result, the agronomic effectiveness of TCSS calculated from Pdff value (in comparison with TSP treatment) was 102%, while the AE of TCSS estimated from CPU value (in % TSP) was 64%, which is attributed to microbial activity stimulation inducing P immobilization onto soil constituents and microbial biomass during plant growth. The high C/N ratio of TCSS stimulated soil microbial biomass that competes with plant roots to acquire nutrients, such as P. As a consequence, the P taken up from either native soil or TCSS decreased in similar proportions. The AE value calculated with Pdff% took into account these interactions between soil, plant, and microbial biomass, and is less dependent on operational conditions than the AE value calculated with %Precovery.